Peningkatan Hasil Belajar Siswa Kelas 4 SD N Tangkisan Pos Dengan Pendekatan Deep Learning Pada Mata Pelajaran Matematika - Ferryka, Putri Zudhah; Suwartini, Sri; Rofisian, Nela; Rahmawati, Isna (Universitas Muhammadiyah Magelang, 2026)
The purpose of this study is to determine the improvement in mathematics learning outcomes of 4th-grade students at SD Negeri Tangkisan Pos using a deep learning approach. This study is motivated by the low learning outcomes of students, as evidenced by 72.2% of students still being below the Minimum Completeness Criteria (KKTP). This is due to the lack of innovation by teachers in conducting learning, making it difficult for students to understand the learning material. The type of research used is classroom action research using the Kemmis & Mc Taggart model. This research model consists of four stages: planning, action implementation, observation, and reflection. The subjects of this study were all 4th-grade students at SD Negeri Tangkisan Pos, consisting of 18 students, with 12 male students and 6 female students. Data collection techniques used included observation sheets, learning test result measurements, and documentation. The data analysis technique used was desk analysis.